A New Genus and New Species of Sciaenidae from the Gulf of Panama (Perciformes: Sciaenidae) - Chao, Ning Labbish; Béarez, Philippe; Robertson, Ross (Revista de Biología Tropical, 2001)
Paranebris bauchotae, a new genus and species of sciaenid from the Gulf of Panama is described from three specimens (138-212 mm SL). It is distinguished from all other sciaenids by having granulated tooth plates on the jaws and the premaxillary tooth plates that are exposed laterally of the lower jaw when the mouth is closed. The new genus shares the following characters with the New World genus Nebris: a thick fleshy and cartilage gap present between premaxillary bones where the ascending processes form an A-frame arch; gas bladder with a pair of long U-shaped appendages; and a thick, oval-shaped sagitta with deeply grooved caudal section of the sulcus. Paranebris bauchotae is distinct from all Nebris species in having a firmer interorbital skin and scale cover (spongy to the touch in Nebris), a larger eye (6-7 vs. 8-12 times in head length) and large ctenoid scales (vs. small and cycloid in Nebris).